2004
DOI: 10.1002/anie.200353207
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Gold(I) Complexes: Highly Alkynophilic Catalysts for the exo‐ and endo‐Cyclization of Enynes

Abstract: Alkynophilic cationic gold(I) complexes are very active catalysts for reactions of enynes that proceed exclusively through cyclopropyl carbene complexes as intermediates (see scheme). With such catalysts, the first examples of endocyclic skeletal rearrangements under mild conditions have been observed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
268
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 586 publications
(285 citation statements)
references
References 52 publications
9
268
0
6
Order By: Relevance
“…Alternatively, the cyclopropanation can be envisioned to occur step-wise via initial reaction of alkene with alkenyl cation 57 (Scheme 13), followed by nucleophilic interception of the resulting carbocation by alkenyl platinum. DFT calculations, which were carried out by Echavarren and co-workers, [11] suggested that in the case of Au(I) catalysis cyclopropanation proceeds directly via a single transition state located on the potential energy surface. In the absence of external nucleophile, highly electron deficient carbene 63 can undergo [1,2] alkyl shift to give zwitterion 64.…”
Section: Scheme 2 a C H T U N G T R E N N U N G (Pphmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the cyclopropanation can be envisioned to occur step-wise via initial reaction of alkene with alkenyl cation 57 (Scheme 13), followed by nucleophilic interception of the resulting carbocation by alkenyl platinum. DFT calculations, which were carried out by Echavarren and co-workers, [11] suggested that in the case of Au(I) catalysis cyclopropanation proceeds directly via a single transition state located on the potential energy surface. In the absence of external nucleophile, highly electron deficient carbene 63 can undergo [1,2] alkyl shift to give zwitterion 64.…”
Section: Scheme 2 a C H T U N G T R E N N U N G (Pphmentioning
confidence: 99%
“…In 2004, as a part of their comprehensive study of gold-based catalysis of enyne cycloisomerizations, Echavarren and co-workers reported that cationic gold complexes were exceedingly effective in promoting alkoxycarbocyclizations of a wide range of 1,6-enynes. [11,28] A representative scope of this process, as well as the typical reaction conditions, is shown in Scheme 27.…”
Section: Formation Of Alkyl-and Alkenylmethylenecyclopentanes and Cycmentioning
confidence: 99%
“…Useful reactions for the formation of allylboronates are expected to be developed using this approach. 23 In summary, a borylative cyclisation leading to alkenylboronates has been developed. An appropriate choice of ligands allows formation of allylboronates.…”
Section: View Article Onlinementioning
confidence: 99%
“…Final desilylation by means of potassium fluoride delivered 5 possessing the desired terminal triple bond in 63% yield. We then examined the reactivity of 5 in the presence of catalytic amounts (4 mol%) of Echavarren's cationic gold(I) catalyst 28 in dichloromethane at room temperature, conditions that proved to be optimal in our previous study. We were delighted to observe the sole formation of furan derivative 6, which also readily occurred with only 2 mol% of the catalyst without hampering substrate conversion.…”
Section: Resultsmentioning
confidence: 99%